The Effect of Micro-Entrepreneurship on Migration Plans of Young Adults in Rural Sub-Saharan Africa and the Mediating Role of Subjective and Economic Well-Being - Christian Stöhr (Junior Management Science (JUMS), 2022)
Entrepreneurship can make a valuable contribution to global poverty reduction. However, poverty is often narrowly defined in terms of income and gross domestic product. Thus, a deep understanding of the impact of entrepreneurship on the development of the Global South cannot be obtained. To address this issue and uncover the transformative potential of entrepreneurship, this paper proposes a model in which both economic and subjective well-being mediate the relationship between micro-entrepreneurship and migration plans of young adults in rural sub-Saharan Africa. The results provide tentative evidence of a negative impact of micro-entrepreneurship on migration plans. Further, it is shown that subjective well-being explains part of the negative association between micro-entrepreneurship and migration plans. While those results hold for entrepreneurs in low-income countries and agricultural entrepreneurs, no evidence is found for entrepreneurs in middle/high-income countries and non-farm entrepreneurs. Contrary to expectations, the mediating role of economic well-being is not significant for either the entire group of micro-entrepreneurs or its subgroups. Finally, economic and subjective well-being as measures of poverty alleviation are found to be positively correlated.
Keywords: 650; Entrepreneurship; Migration; Subjective well-being; Sub-saharan africa